Flow properties of sugar beet pulp cellulose and intrinsic viscosity-molecular weight relationship - Togrul, H; Arslan, N (Elsevier Sci Ltd, 2003)
Cellulose was extracted with 5, 10, 15% NaOH at 25, 35, 45 degreesC for 10, 16, 22 It from defatted, protein, pectin and hemicellulose free, delignified sugar beet pulp. Extraction with 10% NaOH at 35 degreesC for 22 h gave the highest yield of the removal of substances with the exception of cellulose. The effects of temperature and concentration on the viscosity of sugar beet pulp cellulose solutions were examined at different temperatures and concentration levels. Twenty-eight different model equations that describe the combined effects of temperature and concentration on the viscosity were derived. Theoretical models describing the temperature and concentration dependence of viscosity were fitted to the experimental data and the model parameters in equations. were. determined by multiple regression analysis of the experimental data in the temperature range 10-60 degreesC and in the concentration range 0.5-10 kg/m(3). The viscosity of cellulose from sugar beet pulp can be predicted by the single equation: ln eta = -2.8C(0.0186) + 1031C(0.0211)/T + 2654 exp(0.1896C)/T-2. The average molecular weight was measured by light scattering technique. Intrinsic viscosities and molecular weights of cellulose obtained at different extraction conditions ranged between 0.347-0.0836 m(3)/kg and 303,200-893,500 kg/kg mol, respectively. The molecular weight dependence of the intrinsic viscosity of the sugar beet pulp cellulose solutions was expressed by Mark-Houwink-Sakurada equation. The intrinsic viscosity-molecular weight relationship was found as eta(i) 2.313 X 10(-6)(M-w,M-ave)(0.7665). (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: sugar beet pulp; cellulose; temperature and concentration dependence; intrinsic viscosity; molecular weight